Enzymes C1r and C1s may show progression of a type of skin cancer called keratinocyte‐derived cutaneous squamous cell carcinoma. (28th February 2020) - Riihilä, P.; Viiklepp, K.; Nissinen, L.; Farshchian, M.; Kallajoki, M.; Kivisaari, A.; Meri, S.; Peltonen, J.; Peltonen, S.; Kähäri, V.‐M.
Summary: The incidence of skin cancers is increasing worldwide. The epidermis is the surface layer of the skin and the main cell type is the keratinocyte. Keratinocyte‐derived cutaneous squamous cell carcinoma (cSCC) is the most common metastatic (meaning it can spread) skin cancer and it is responsible for 20% of skin cancer related deaths. The main risk factor for cSCC includes long term exposure to sun ultraviolet radiation. The progression of cSCC is as follows: it starts in a premalignant form (not yet cancerous) called actinic keratosis (AK), then becomes locally restricted cSCC, then cSCC in situ (cSCCIS), and eventually becomes invasive and metastatic cSCC. This research, from Finland, aimed to find biomarkers (chemicals in the body which act as signs of a disease) which could predict the progression and aggressiveness of cSCC. The authors found significantly elevated levels of mRNA (messenger molecules) for enzymes called C1r and C1s (which play a role in our immune system), in cSCC cells and tumors compared to normal epidermal keratinocytes and normal skin, respectively. Abundant expression of C1r and C1s by tumor cells was detected in invasive cSCCs and in an aggressive form of cSCC (recessive dystrophic epidermolysis bullosa‐associated cSCC), whereas the expression of C1r and C1s was lower in cSCCIS, actinic keratosis, and normal skin tissue samples. The roles of C1r and C1s in cSCC cells were investigated by knocking down (reducing) the expression of C1r and C1s, and through complex methods, this was shown to potentially suppress growth of cSCC tumours. These results provide evidence that tumor cell‐derived C1r and C1s play a part in the progression of cSCC and identify them as biomarkers and possible treatment targets in cSCC. This is a summary of the study: Tumour‐cell‐derived complement components C1r and C1s promote growth of cutaneous squamous cell carcinoma Abstract : Linked Article:  Riihilä et al. Br J Dermatol 2020; 182 :658–670